Automated low cost house demand forecasting for urban area - Noor, Yasmin Zainun; Muhd, Zaimi Abd. Majid (Penerbit Universiti Sains Malaysia, 2004)
Historically, urbanization was the product of industrial expansion and rapid economic growth. In developing country however, the process has been characterized by rapid urban growth without corresponding economic growth of the cities. This resulted in the emergemve of the informal sector and squatter settlements. In Malaysia, urbanization is expexted to continue, with the Department of Statistics projecting the urban population at 64% of total population by the year 2020.